A new treatment for ulcerative colitis: Intracolonic Bifidobacterium and xyloglucan application. (July 2020) - Bozkurt, Huseyin Sancar; Kara, Banu
Ulcerative colitis (UC) pathogenesis includes the altered gut microbiota, environmental factors, and human immune and genetic predisposition. Recently, its association with reduced bifidobacteria quantity in the microbiota is reported. Xyloglucan, a plant-based prebiotic oligosaccharide, causes increase in bifidobacteria quantity. In this article, we share the results of our UC cases treated by intracolonic single-dose administration of Bifidobacterium animalis subsp. lactis and xyloglucan combination. Intracolonic single-dose administration of 200 billion colony-forming units (CFUs) of B. animalis subsp. lactis and 4 g of xyloglucan combination was administrated to 10 severe UC patients, who were either unresponsive or had inadequate response to treatment. All patients continued treatment after the procedure. Treatment responses were evaluated by colonoscopic, laboratory, and clinical examination after 6 weeks. Intracolonic single-dose administration of B. animalis subsp. lactis and xyloglucan was found effective in the mucosal healing and resolution of colonic symptoms in UC patients. Intracolonic administration of B. animalis subsp. lactis and xyloglucan in UC is a new single-strain and strain-specific prebiotic combination method. It is easy to apply and has no observable side effect. Its effectiveness on mucosal healing could be attributed to the enhancement of non-stimulatory status and biodiversity in colonic mucosa. Nonetheless, it is still necessary to develop diagnostic strategies to determine the patients to whom this method would be the most applicable.